Slouching toward tyranny : mass incarceration, death sentences and racism - Ingle, Joseph B. (Joseph Burton), 1946- (Algora Publishing, 2015)
As a pastor to Death Row inmates across the South and as a powerful advocate appealing to prison wardens, lawyers, judges, and legislators, Joseph Ingle has come to some shocking conclusions about the United States, champion of human rights throughout the world. He began to recognize another aspect to US history: systematic oppression imposed by the very people who founded the country. The book is part personal experience, part history: the history of systematic destruction of minorities in America, from colonial days to now, by physical slaughter and by legal and judicial means.